Interaksi AtMEK1-EXGT pada Arabidopsis thaliana pada Saat Terjadi Pelukaan - Toto Hadiarto; Fumio Nanba (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2008)
Proteininteractions occur within cellular level of stimulated plantcells to relay signals from receptors to production of response.AtMEK1-EXGT interaction had been detected in nontreatedArabidopsis. In this research, interaction betweenAtMEK1, a mitogen-activated protein kinase kinase ofArabidopsis thaliana, and EXGT, endoxyloglucan transferase,after the plant was wounded was examined usingco-immunoprecipitation and in vitro phosphorylation assay.The results demonstrated that EXGT interact with AtMEK1soon after and 10 minutes after wounding. In addition,AtMEK1 phosphorylation activity increased when increasedlevel of EXGT was incorporated into the reaction mixture.These indicate that EXGT amplifies wound-caused phosphorylationactivity of AtMEK1. The results elucidate part ofthe AtMEKK1-AtMEK1-AtMPK4 cascade which is stimulatedby wounding. How the complex interaction between EXGT,AtMEK1 and AtMPK4 fits within the cascade is remained tobe uncovered.